Análisis comparativo de los resultados de Dióxido de azufre (SO2) y Dióxido de Nitrógeno (NO2) obtenidos de datos del sensor Tropomi y por mediciones de estaciones de monitoreo de calidad del aire en la ciudad de Bogotá (2025)
This study presents a comparative analysis based on the existing correlation between the concentrations of the pollutants Sulfur Dioxide (SO2) and Nitrogen Dioxide (NO2), obtained from data provided by the Tropomi sensor and from the measurements of the Bogotá Air Quality Monitoring Network (RMCAB), during the time period that included the months of January, February, and March of 2023. Based on the statistical analysis and the spatiotemporal distribution trends of the evaluated pollutants, it was observed for NO2 that there was an evident degree of similarity in the behavior of the concentrations measured at the surface and those estimated at the tropospheric level. As for SO2, it was observed that the surface concentration records of SO2 vary significantly from the data provided by the Tropomi sensor